2016
DOI: 10.3389/fnins.2016.00561
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate Prevents Placental Ischemia-Induced Increases in Brain Water Content and Cerebrospinal Fluid Cytokines in Pregnant Rats

Abstract: Magnesium sulfate (MgSO4) is the most widely used therapy in the clinic to prevent the progression of preeclampsia, a hypertensive disorder of pregnancy, to eclampsia. Eclampsia, manifested as unexplained seizures and/or coma during pregnancy or postpartum, accounts for ~13% of maternal deaths worldwide. While MgSO4 continues to be used in the clinic, the mechanisms by which it exerts its protective actions are not well understood. In this study, we tested the hypothesis that MgSO4 protects against placental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 69 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…Previously, we reported that eotaxin (CCL11) is increased in the cerebrospinal fluid of placental ischemic dams [42,49]. In the current study, we found increased levels of eotaxin in the brains of fetuses exposed to placental ischemia.…”
Section: Discussionsupporting
confidence: 65%
“…Previously, we reported that eotaxin (CCL11) is increased in the cerebrospinal fluid of placental ischemic dams [42,49]. In the current study, we found increased levels of eotaxin in the brains of fetuses exposed to placental ischemia.…”
Section: Discussionsupporting
confidence: 65%
“…Both preeclampsia patients and the rat model of placental ischemia are characterized by increased levels of circulating and placental inflammatory cytokines during pregnancy. Importantly, we recently showed that cerebrospinal fluid levels of the cytokines/chemokines eotaxin, IL-2, IL-17, and IL-18 are increased in the placental ischemic rat (Warrington, 2015; Zhang and Warrington, 2016). In this study, we show that 2 months after delivery, rats exposed to placental ischemia have increased levels of the anti-inflammatory cytokines IL-4 and IL-10, and a significant increase in the pro-inflammatory cytokines, IL-17, IL-1α, IL-1β, Leptin, and MIP-2 in the posterior cortex where water content was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action by which magnesium sulfate exerts its effects is unknown, but despite this limitation, it is widely considered a neuroprotective agent capable of reducing BBB permeability in animal models of brain injury ( Li et al, 2017 ). Furthermore, a recent study demonstrated that magnesium sulfate reduced the water content in the anterior cerebrum, as well protein, cytokine, chemokine and VEGF levels in cerebrospinal fluid of rats subjected to the RUPP procedure ( Zhang and Warrington, 2016 ). The above findings are important since the transport of drugs and endogenous mediators across the choroid plexus, which constitutes the blood-cerebrospinal fluid barrier, is a subject that is receiving increasing interest.…”
Section: Pharmacological Management Of Preeclampsiamentioning
confidence: 99%